Kinetic and Thermodynamic Study Removal of Co(II) Using Biosorbent Spirulina sp. in Aqueous Solution - Risfidian Mohadi; Hermansyah Hermansyah; Poedji Loekitowati Hariani; Zazili Hanafiah; Hilda Zulkifli (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Kinetic and thermodynamic adsorption study of Co(II) ions from aqueous solutions by dried Spirulina sp. biomass was investigated in the batch system. The Spirulina sp. was isolated and cultured from algae swamp ecosystem in South Sumatera. The adsorption properties of Co(II) onto dried Spirulina sp. biomass was studied by the influence of contact time, initial metal ion concentration and reaction temperature. The experimental results were the rate of adsorption followed the second-order kinetic model with the rate of reaction k2 is 0.023 g mg-1 min-1  and the thermodynamic studies showed that the adsorption was well fitted to the Langmuir’s model, and the amount of Co(II) removed from solution increased with increasing Co(II) concentration with the higher adsorption energy was 10.38 kJ/mol at 30 °C.Keywords: Spirulina sp, Co(II), adsorption, algae swamp, South Sumatera